The role of stress and its impact on the formation of occupational burnout - Olaf Lisowski; Mateusz Grajek (Kazimierz Wielki University, 2023)
The term "stress" is customarily used in connection with environmental pressures and adaptation to changing environmental conditions, but also in reference to the body's psychological and physiological response to them. In the understanding presented, adaptive demands are called stressors, their effects are called stress or stressful situations, and methods and techniques aimed at reducing these effects are called ways of coping with stress. Stress can also be understood as a "product" of inappropriate coping with the challenges of everyday life. The differentiation between stress as a process and stressor as a factor makes it easier to understand the issue and its impact on life and the development of mental illnesses.